A study on classroom management at UiTM Sarawak branch Samarahan campus / Gaddam Jagmohan Das ... [et al.] - Das, Gaddam Jagmohan; Goy, Siew Ching; Singh, Derick; Rajaretnam, Sailaja; Khong, Heng Yen; Jalil, Susanna William (2001)
UiTM provides education and training in a wide range of science, technology, business studies and other professional courses for over 60,000 full-time students, above 5000 part-time students and about 9,000 students in distance learning programmes ill different campuses spread over the whole country. UiTM Sarawak Branch, Samarahan Campus (UiTMSBSC) is one of the two branch campuses functioning in East Malaysia for the education, economic and social development of Bumiputeras in Sarawak and Sabah.